STUDY OF COMPOSITION AND VEGETATION POTENTIAL OF PRODUCTION FOREST IN KPH DAMPELAS TINOMBO SOUTH TINOMBO SUB-DISTRICT, PARIGI MOUTONG DISTRICT - Palaguna, Hamzari; Rahman, Abdul; Anwar, Anwar (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
Forests as a gift and mandate of God Almighty bestowed on the Indonesian Nation is a priceless natural wealth, therefore it must be grateful. Therefore, the forest must be managed and utilized wisely as a manifestation of gratitude to Allah SWT. The production forest area in the KPH Dampelas Tinombo area that is included in Parisan Agung Village, Dampelas Sub-district, which is indicated to have suffered damage, has an area of around 410 hectares. Therefore, a study on the composition and potential of production forests in Parisan Agung Village is needed for planning the utilization and development of plantation forests with the aim of providing welfare for the people living around the forest area without changing its main function. This research was carried out for 3 months starting from January to March 2020. The location of this research is located in the production forest in the KPHP Model Dampelas Tinombo area which is included in the Parisan Agung Village area, Dampelas District, Donggala Regency, Central Sulawesi Province. The composition of vegetation types of Parisan Agung Village production forest consists of 28 types of vegetation. at the tree level in the plot as many as 165 individuals from 25 types of vegetation while pole level vegetation as many as 140 individuals from 25 types of vegetation, stake level as many as 145 individuals from 28 types of vegetation and seedling level as many as 154 individuals from 28 types of vegetation. While the potential volume of trees in the observation plot is 162.53 m3 from 165 individuals, the bayas species has the largest volume with 13.17 m3 and the pole level volume in the observation plot is 17.89 m3 from 140 individuals, the prupuk species has the largest volume with 1.63 m3.